2022
DOI: 10.3390/cancers14153736
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Biomarkers Predictive of Efficacy Outcome and Immune-Related Adverse Events in Advanced Gastrointestinal Cancers Treated with Checkpoint Inhibitors

Abstract: Background: Gastrointestinal cancers constitute a major burden of global cancer mortalities. In recent years, the advent of immune checkpoint inhibitors has greatly improved the survival of patients with advanced gastrointestinal cancers, while predictive biomarkers of treatment efficacy and toxicities are still unmet demands. Methods: In our retrospective study, patients with advanced gastrointestinal cancers who received single or double immune checkpoint inhibitors in the Department of Gastrointestinal Onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Previous treatment was described in four articles ( 15 18 ), one of which included previous antitumor regimens as one of the criteria when including patients ( 16 ). Six articles included only patients who received ICI monotherapy ( 15 , 16 , 19 22 ). The remaining studies were unrestricted, and they included patients who received ICI in combination with other antitumor treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Previous treatment was described in four articles ( 15 18 ), one of which included previous antitumor regimens as one of the criteria when including patients ( 16 ). Six articles included only patients who received ICI monotherapy ( 15 , 16 , 19 22 ). The remaining studies were unrestricted, and they included patients who received ICI in combination with other antitumor treatments.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the results varied somewhat between studies. A majority of studies suggested that both ratios were negative predictors for irAEs (neutrophil–lymphocyte ratio > 2.86 [ 48 ], ≥3 [ 42 , 49 ], ≥3.2 [ 33 ], ≥5 [ 50 ], >5.3 [ 31 ], and no specific cutoff [ 34 , 38 , 51 ]; platelet–lymphocyte ratio ≥ 180 [ 54 ], >300 [ 52 ], >534 [ 31 ], and no specific cutoff [ 38 ]). However, several studies could not confirm the negative association of both ratios with irAEs [ 29 , 33 , 35 , 36 , 37 , 40 , 46 , 47 , 51 , 52 , 53 , 54 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…A majority of studies suggested that both ratios were negative predictors for irAEs (neutrophil–lymphocyte ratio > 2.86 [ 48 ], ≥3 [ 42 , 49 ], ≥3.2 [ 33 ], ≥5 [ 50 ], >5.3 [ 31 ], and no specific cutoff [ 34 , 38 , 51 ]; platelet–lymphocyte ratio ≥ 180 [ 54 ], >300 [ 52 ], >534 [ 31 ], and no specific cutoff [ 38 ]). However, several studies could not confirm the negative association of both ratios with irAEs [ 29 , 33 , 35 , 36 , 37 , 40 , 46 , 47 , 51 , 52 , 53 , 54 ]. Both raw cell counts and ratios from multiple studies suffered from the heterogeneity of the cutoffs, and the harmonization of the cutoff is necessary before this can be utilized in real-world settings.…”
Section: Biomarkersmentioning
confidence: 99%
“…Recently, there has been a growing interest in the field of peripheral blood to identify non-invasive, cost-effective, easily accessible, and promising prognostic biomarkers to predict prognostic and toxicity of ICIs [ 10 ]. Consequently, many peripheral blood inflammatory-nutritional indices such as albumin, lactate dehydrogenase (LDH), neutrophil-to-lymphocyte ratio (NLR), derived NLR (dNLR), and C-reactive protein-albumin ratio (CAR) were found to link with metabolic homeostasis and affect the survival outcomes of ICIs [ 11 17 ].…”
Section: Introductionmentioning
confidence: 99%